Construction and Validation of a risk model Based on Cuprotosis-related LncRNAsin Colon Adenocarcinoma: Risk model Based on Cuprotosis-related LncRNAsin - Tan, Pufang; Hao, Renshan; Zhu, Qi; Wu, Xiao; Zhang, Ye (Cellular and Molecular Biology, 2022)
Cancer cells are significantly impacted by copper-induced cell death (cuprotosis). Long noncoding RNAs (lncRNAs) are crucial in the developmental process of colon adenocarcinoma (COAD). The ability of Cuprotosis-related lncRNA biomarkers to predict COAD prognosis, on the other hand, remains uncertain. This research intended to build a model of risk specifically for COAD based on cuprotosis-related lncRNAs. Univariable Cox, LASSO, as well as multivariable Cox analyses were utilized to identify cuprotosis-related lncRNAs linked with prognosis, and a model of risk was constructed. Five cuprotosis-related lncRNAs, AC008494.3, SNHG7, LINC02257, ZEB1-AS1, and AC116913.1, were discovered from the training set and utilized for the creation of a predictive model of risk. In the training and testing sets, as well as the total patient population, overall survival was dramatically lower for the high-risk patients than for the low-risk patients. The model's prognosis validity was confirmed by time-dependent areas under the ROC curves, which were identified as an independent prognosis element in multivariable COX regressive analysis. The established cuprotosis-related lncRNA-based predictive risk model was linked to chemotherapeutic sensitivity.in COAD patients, a model of risk based on five cuprotosis-related lncRNAs can predict prognosis and chemotherapeutic effectiveness.